Розрахунок міцності залізобетонних елементів на основі розрахункового опору залізобетону - Pavlikov, Andrii; Harkava, Olha; Kelvis, Atembemoh (Збірник наукових праць Галузеве машинобудування будівництво, 2022)
The paper presents the simplified deformation model for the section analysis of reinforced concrete members, which is considered as composite material formed of concrete and reinforcement. On this basis, it is proposed to use the design strength of reinforced concrete. This allows to reduce the section analysis of reinforced concrete members to the methodology of calculations introduced in the classical “strength of materials”, which contributes to a significant simplification and acceleration of the design process of both single members and structures in general. This approach to the section analysis of reinforced concrete members makes it universal for all deformation types of reinforced concrete members. The paper demonstrates and confirms the possibility of using the developed methodology in the bearing capacity calculations of bended reinforced concrete members.
Keywords: бетон; арматура; залізобетон; розрахунковий опір; , розрахунок